IJCM_45A: Inter-district variation in preterm deaths identified by a perinatal death audit: a health system intervention research - Rao Suchetha S; Kamath Nutan; Kushtagi Pralhad; Kumar Harsha H N; Baliga B Santharam (Wolters Kluwer Medknow Publications, 2024)
Background: Analyzing preterm deaths is crucial due to the significant contribution of preterm babies to neonatal mortality rates. However, there is no universal perinatal death (PND) audit system in India Objective: To analyze the preterm deaths in two districts of Karnataka with study model of PND audit Methodology: Hospitals with maternal and child care facilities which met inclusion criteria in Dakshina Kannada (DK), high performing and Koppal (KPL),low performing districts were included after institutional ethics committee approval and permission from Mission Director, National Health Mission, Directorate of Heath and Family Welfare Services, Government of Karnataka. A PND audit system was designed. Personnel with training in medico-social history taking were utilized for data accumulation. Causal analysis of death as certified by independent expert panels and certifying physician was carried out and was compared for functionality. To determine optimality of care, facilities were categorized depending upon available levels of maternity and neonatal care. Preterm deaths during the one-year study period with complete data were analyzed. Results: 119 preterm deaths in DK and 97 preterm deaths in KPL were analyzed. In utero transfer was 81.5 % in DK and 11.3% in KPL. More preterm deliveries were documented in public hospitals in both districts. Deaths of preterm babies in private hospitals at KPLwas 41.2% against 27.8% private deliveries. In KPL 22.6% babies died at home despite delivering in hospitals. Risk factor documentation was poor in both districts. Expert committee review increased preventability assertion from 7.5 to 11.7% in DK, 2 to 62.8% in KPL. Conclusion: Auditing perinatal deaths and analysing preterm deaths resulted in identification of specific deficiencies in healthcare system. DK had reasonably good facilities but KPL had serious concerns. The study model enhanced the preventability assertion in preterm deaths